Visual Strategy as an Approach To Promotion of Youth Local Brands - Yahya, Elden; Aulya, Dyla; Mardhatillah, Siti (LPPM Universitas PGRI Sumatera Barat, 2024)
The use of visual strategies in promotional approaches is the main key in realizing an informative shopping experience in this digital era. Focuses on stunning visual communication design to convey deeper information about a product. The aim of this research is to determine the visual approach strategy in promotion of local youth brands. This research method is qualitative with a case study research design. The data sources for this research are primary data and secondary data. Primary data was obtained through data collection by conducting interviews and observations. Secondary data is obtained through data that supports research, such as scientific articles and books. The visual strategy approach to promotion of local youth brands can be done through several things, namely photography, design elements, copywriting and layout. These four strategies will be combined into one unit to create a visual strategy that adapts to the needs and desires of the audience. So researchers draw the conclusion from this research that the use of visual strategies in a promotional approach is the main key in creating an informative shopping experience in this digital era. Focuses on stunning visual communication design to convey deeper information about a product